CYBERSECURITY SKILLS AT THE PERSONAL AND INSTITUTIONAL DOMAINS IN PROTECTING MANAGEMENT INFORMATION SYSTEMS: AN APPLIED STUDY - Assistant Lecturer Zahraa falih oudah (Journals Park Publishing, 2025)
The research aimed to identify the cybersecurity skills necessary for protecting management information systems among students of Management Information Systems faculties at both the personal and institutional domains, and to assess the students' proficiency in these skills, identify the major challenges impeding their development, and suggest appropriate strategies for their enhancement, The research sample consisted of (32) male and female students from the fourth year at a Management Information Systems college in one of the Iraqi universities, The research tool was a questionnaire designed to measure cybersecurity skills at both the personal and institutional domains, The statistical analysis revealed a relative deficiency in some cybersecurity skills compared to the assumed average (4) on the five-point Likert scale, with major challenges identified, including lack of technical expertise and limited practical training opportunities, The research recommended the integration of cybersecurity skills into academic curricula and the design of continuous training programs to enhance students' cybersecurity awareness and skills.
Keywords: Cybersecurity; Cybersecurity skills; Management Information Systems.